ISU-ISU KRITIS DALAM PENDIDIKAN ISLAM PERSPEKTIF PEDAGOGIK KRITIS - Tabrani ZA (Islam Futura, 2014)
Conceptualization and theorization of Islamic education has been less attention to aspects of his involvement in the process of social transformation. In addition, Islamic Education also seems to have developed to the maximum language of language of critique and possibility. Literature related to Islamic education from the past until now tend to be dominated by a normative approach, with little practical in many aspects and ignore the discursive historical-empirical level. Until now, even the idea of the concept of Islamic education promoted by thinkers of contemporary Islamic education has not touched the real issues related to humanitarian issues. There is no attempt to draw normative concepts, ideal and abstract, to the empirical-sociological level. When the concept of Islamic education is faced with the problems of empirical-sociological and just wrestle on normative issues, the Islamic education could be stuck in the ideology of positivism that tend to deny the importance of criticism of social reality. Therefore, Islamic education needs to balance-normative aspects of religious and historical.